PENGARUH AGRESIVITAS PAJAK DAN MANAJEMEN LABA RIIL TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI MODERASI - Vivian Angelina; Estralita Trisnawati; Sriwati (Fakultas Ekonomi Universitas Tarumanagara, 2025)
The value of company is reflected by company's share price which can be increased in several ways. This research examines the influence of tax aggressiveness and real earnings management on firm value, and examines the role of institutional ownership as a moderator. The research sample is transportation sector companies listed on the Indonesia Stock Exchange during 2018-2022. This sample selection used a purposive sampling method, the number of samples used in this research were 21 companies. Research shows that tax aggressiveness has an effect on company value, while real earnings management has no effect on company value. Research on the role of institutional ownership shows that institutional ownership does not moderate tax aggressiveness on company value, but does moderate real earnings management on company value.